Evaluasi & Analisis Rencana Perubahan Jalur Ventilasi Untuk Kebutuhan Lubang Pendididikan Tambang Bawah Tanah Ombilin 1 (Sawahluwung) PT. Bukit Asam Tbk - UPO - Akman Syarif; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Bukit Asam Tbk Ombilin Mining Unit (UPO-PTBA) is the oldest underground coal mine in Indonesia, due to the activity of the penambangannya has been performed since the colonial Netherlands.Ventilation system in underground mine Sawahluwung using suction system (exhaust) air out the quantity of 35.10 m3/s, while the quantity of incoming air of 34.50 m3/s through the three holes of entry i.e. Adit Sawahluwung + 214 of 23.00 m3/s, Adit Sawahluwung + 223 of 6.50 m3/s and head of Sapan II of 5.00 m3/s. The amount of air entering the air out there is a difference of 0.60 m3/s caused by air leaks in the duct wall Mine Fan.Hand in hand towards post-war mines, PTBA UPO plans make preparing hole and education as a means of education for the world of education and society, then closing and pengedaman done on the area J6-J8, J7-J9, J1-Bak Pumps LS II. The pattern of air flow enters starts from the Adit Sa.Keywords: The Need Of Air, Ventilation System, Tunnel Education,Kepmen.